Financial Literacy and Preparation for Retirement - Henriette Prast; Arthur van Soest (Intereconomics, 2016)
To meet the challenges of an ageing population, eligibility ages for state pensions have increased, early retirement arrangements have been abolished, and a substantial part of the risk and responsibility for an adequate standard of living after retirement has been shifted from the government, employers and pension funds to individuals and private households. Consequently, policy makers have become more concerned with whether individuals are able to make pension-related decisions that are in their own best interest.
Keywords: 330; Altersgrenze; Finanzwissen; Private Finanzplanung; Altersvorsorge; Politische Kommunikation; OECD-Staaten